2015
DOI: 10.1007/s10706-015-9868-6
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Stress State in Two Adjacent Backfilled Stopes Within an Elasto-Plastic Rock Mass

Abstract: Backfill is used in the mining industry to improve the stability of underground openings and reduce the environmental impact due to the surface disposal of mine wastes. A critical issue for the design of backfilled stopes is the determination of the stress state in the backfill and surrounding rock mass. In recent years, much work has been conducted to assess the stresses in isolated backfilled stopes. Recent work performed by the authors indicates that the stress distribution in a backfilled stope may also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the numerical analyses are very helpful to understand the mechanical response of backfilled stope (Rankine, 2004;Pirapakaran and Sivakugan, 2007;Li and Aubertin, 2009b;Veenstra, 2013;Falaknaz, 2014;Falaknaz et al, 2015aFalaknaz et al, , 2015bFalaknaz et al, , 2015cLi and Aubertin, 2014;Liu, 2017;Liu et al, 2016aLiu et al, , 2016bLiu et al, , 2017Yang et al, 2017a). In this study, FLAC 3D is used to analyse the stability of the exposed backfill.…”
Section: Numerical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the numerical analyses are very helpful to understand the mechanical response of backfilled stope (Rankine, 2004;Pirapakaran and Sivakugan, 2007;Li and Aubertin, 2009b;Veenstra, 2013;Falaknaz, 2014;Falaknaz et al, 2015aFalaknaz et al, , 2015bFalaknaz et al, , 2015cLi and Aubertin, 2014;Liu, 2017;Liu et al, 2016aLiu et al, , 2016bLiu et al, , 2017Yang et al, 2017a). In this study, FLAC 3D is used to analyse the stability of the exposed backfill.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Numerous recent studies have shown that this solution can be valid when the stopes are very large in plane and small in height. For most cases, the arching effect has to be considered for estimating the stresses in backfilled stopes (Aubertin et al, 2003;Li et al, 2003Li et al, , 2005Li and Aubertin, 2009a, 2009bThompson et al, 2012;Falaknaz et al, 2015aFalaknaz et al, , 2015bFalaknaz et al, , 2015cLiu et al, 2016bLiu et al, , 2017. As the arching effect was neglected in the calculation of the lateral pressure along the two side walls and stability analysis of the exposed cemented backfill, the solution of Yang et al (2015) can be rewritten as follows for estimating the minimum required cohesion (FS = 1) of the cemented backfill:…”
Section: Comparison With the Existing Solutionmentioning
confidence: 99%
“…Many studies have found that fractures often develop around fault zones and anticlinal core, and that fracture spacing is positively correlated with regional differential stress [12] [13] [14]. Some researchers have suggested that lithology and combination of fractures may be more significant than regional stress [15] [16] [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%